Additional file 2: of Genomic mechanisms for cold tolerance and production of exopolysaccharides in the Arctic cyanobacterium Phormidesmis priestleyi BC1401 - Chrismas, Nathan; Barker, Gary; Anesio, Alexandre; Sรกnchez-Baracaldo, Patricia (Figshare, 2016)
Circos plot showing P. priestleyi BC1401 contigs that did not map to L. boryana PCC6306. Contigs are ordered according to size in an anticlockwise direction. (PDF 20 kb)